SrTaO2N co-doped with La/Zr as promising photocatalysts for water reduction under visible light illumination. Issue 12 (13th May 2020) - Wang, Ran; Lin, Guoan; Xu, Xiaoxiang
Abstract : La/Zr co-doping preserves visible light absorption of SrTaO2 N, prohibits the formation of defects, improves surface hydrophilicity and charge separation conditions, all of which contribute to an enhanced photocatalytic activity for water reduction. Abstract : La/Zr co-doped SrTaO2 N has been investigated as visible-light-active photocatalysts for water reduction. Unlike previous aliovalent doping that leads to a decrease in light absorption, La/Zr co-doping largely preserves the visible light absorption of SrTaO2 N. More importantly, the La/Zr co-doping not only helps to improve surface hydrophilicity and reduce particle sizes but also effectively inhibits defect formation ( e.g. Ta 4+ ) in SrTaO2 N. These modifications are responsible for significant enhancements in photocatalytic H2 production. AQE as high as 0.84% was achieved at 420 ± 20 nm for Sr0.4 La0.6 Ta0.4 Zr0.6 O2 N ( x = 0.6), which also showed good durability and stability. Further analysis suggests that La/Zr co-doping negatively shifts the conduction band edge positions of SrTaO2 N and contributes to better charge separation conditions.